2001
DOI: 10.1200/jco.2001.19.11.2915
|View full text |Cite
|
Sign up to set email alerts
|

BCR Rearrangement–Negative Chronic Myelogenous Leukemia Revisited

Abstract: Patients with M-bcr rearrangement-negative CML fall into three morphologic subgroups. Disease evolution does not generally involve blastic transformation. Instead, patients show progressive organomegaly, leukocytosis, anemia, and thrombocytosis. Some patients in each subgroup can respond to interferon alfa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
77
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 46 publications
2
77
0
Order By: Relevance
“…1,6,7 Some of these cases have an elevated monocyte count and thus overlap with chronic myelomonocytic leukemia (CMML), an entity now considered as a subtype of MDS/MPD. The molecular pathogenesis of BCR-ABL negative MPDs is poorly understood but a minority of cases present with an acquired reciprocal chromosomal translocation that is amenable to molecular analysis ( Figure 1).…”
Section: Overviewmentioning
confidence: 99%
“…1,6,7 Some of these cases have an elevated monocyte count and thus overlap with chronic myelomonocytic leukemia (CMML), an entity now considered as a subtype of MDS/MPD. The molecular pathogenesis of BCR-ABL negative MPDs is poorly understood but a minority of cases present with an acquired reciprocal chromosomal translocation that is amenable to molecular analysis ( Figure 1).…”
Section: Overviewmentioning
confidence: 99%
“…6 Studies in the early 1990s reported a poor outcome with conventional chemotherapy including hydroxyurea, interferon-a and busulfan. 7,9,11 Morevoer, since the new tyrosine kinase inhibitor imatinib has a selective activity against Abl and Bcr-Abl oncoproteins, 20 it is unlikely to be useful in treating aCML. It was not effective in aCML according to a report of Cortes et al 19 Therefore, allogeneic HSCT remained the only curative option for these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In approximately 25-40% of patients, aCML evolves to acute leukemia, whereas the remainder die of marrow failure with a median survival time of less than 20 months with conventional therapy. [10][11][12] To date only one case report on the outcome of allogeneic hematopoietic stem cell transplantation (HSCT) in a patient with aCML has been published. 13 Therefore, the aim of this study was to evaluate the outcome of HSCT in patients with aCML.…”
mentioning
confidence: 99%
“…The term chronic megakaryocytic leukemia (a) reflects the principal and most constant neoplastic alteration in the disease, (b) corresponds to the nomenclature for most other clonal myeloid disease, (c) assists in decreasing (all too gradually) anachronistic terminology, (d) implies multilineage involvement (leukemia), (e) implies the epiphenomena of marrow fibrosis, osteosclerosis, and fibrohematopoietic extramedullary tumors, and (f) indicates the propensity to terminate in an acute Table 1 The chronic myelogenous leukemias 13 BCR-rearrangement-positive CML BCR-rearrangement-negative CML 14 Chronic myelomonocytic leukemia PDGFRb positive 15 Other genetic abnormalities Juvenile myelomonocytic leukemia Chronic megakaryocytic leukemia (ie idiopathic myelofibrosis) Chronic neutrophilic leukemia a Chronic eosinophilic leukemia a (ie hypereosinophilic syndrome) PDGFRa positive 16 Other genetic abnormalities…”
Section: Classifying Clonal Myeloid Diseasesmentioning
confidence: 99%